2022
DOI: 10.1097/fjc.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanoformulated Polyphenols for Protection Against Cardiovascular Diseases

Abstract: In the past decade, a plethora of research has revealed numerous biological effects of polyphenols, most significantly anticancer and antimicrobial. These versatile, naturally occurring compounds have attracted growing interest among researchers owing to their crucial role in modifying disease progression associated with almost all the body's vital systems, including cardiovascular, neurological, and gastrointestinal systems. However, poor water solubility and rapid metabolism result in low bioavailability, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…Nano-materials are extensively employed in the treatment of persistent injuries due to their ability to trigger multiple molecular processes and cellular pathways that promote angiogenesis and reduce inflammation. 60 Various nano-materials like nanosphere, nano-capsule, nano-emulsion, nano-colloids, nanocarriers, and so on are employed in wound therapy. Among these, metal nanoparticles have displayed favorable properties as they show less in vivo toxicity.…”
Section: Nanotechnology In Wound Therapymentioning
confidence: 99%
“…Nano-materials are extensively employed in the treatment of persistent injuries due to their ability to trigger multiple molecular processes and cellular pathways that promote angiogenesis and reduce inflammation. 60 Various nano-materials like nanosphere, nano-capsule, nano-emulsion, nano-colloids, nanocarriers, and so on are employed in wound therapy. Among these, metal nanoparticles have displayed favorable properties as they show less in vivo toxicity.…”
Section: Nanotechnology In Wound Therapymentioning
confidence: 99%
“…Dietary flavonoids have been extensively studied for their diverse biological activities and have been shown to play significant roles in the prevention of diseases including diabetes, cardiovascular diseases, osteoporosis, and cancer. There has been controversy regarding the bioavailability of dietary flavonoids. Some studies consistently showed dietary flavonoids exhibited limited absorption and low bioavailability. However, other studies indicated that the absorption and bioavailability of some flavonoids were higher than previously believed. , Nevertheless, given the importance of high bioavailability in effectively exerting physiological functions, improving the bioavailability of dietary flavonoids has become a crucial issue of concern. This issue presents a significant challenge in developing and utilizing dietary flavonoids as dietary supplements for human health and requires substantial research.…”
Section: Introductionmentioning
confidence: 99%
“…By reviewing previous studies, we found that researchers often focused on the bioavailability of flavonoids in isolation, neglecting the influence of dietary nutrients. , However, human diets typically consist of a combination of flavonoids and essential macronutrients, such as lipids, carbohydrates, and proteins. These dietary nutrients can potentially affect the bioavailability of flavonoids. Some researchers have explored the changes in the flavonoid transmembrane transport behavior under the influence of carbohydrate or protein nutrient systems.…”
Section: Introductionmentioning
confidence: 99%